THE EFFECT OF VERTICAL INTEGRATION ON FINANCIAL PERFORMANCE (An analytical study in the General Company for Fertilizer Industry - Southern Region) - Prof.Dr.Hashim Nayef Hashim Al-Hachim; Adnan Saad Tuama Al-Sukaini (Galaxy International Interdisciplinary Research Journal, 2023)
The study aims to reveal the correlation and the effect of (vertical integration) as an independent variable on (financial performance) as a dependent variable. The problem of the study was represented in a main question (what is the effect of vertical integration on the financial performance of the company) ?